Urban and tourism development projects for Cities Citadels (Aleppo and Erbil) - Akram, Omar Khasro; Ismail, Sumarni; Franco, Daniel Jose (IJETMAS, 2016)
This research addresses the points present in the creation of a theoretical framework about the strategies adopted in the development of the Aleppo and Erbil Citadels. These particular citadels were chosen not just because of, according to the urban and cultural aspects, they have many shared points, but also because Aleppo’s Citadel is consideredanuniversal paradigm of which many positives aspects are present in the development strategy. It is focused the comparison of these points with the ones adopted by Erbil’s Citadel, identifying the positive and negative aspects in a way to achieve an optimal urban development strategy for City Citadels.